Effects of Vivifrail multicomponent intervention on functional capacity: a multicentre, randomized controlled trial. Issue 2 (11th February 2022) - Casas‐Herrero, Álvaro; Sáez de Asteasu, Mikel L.; Antón‐Rodrigo, Iván; Sánchez‐Sánchez, Juan Luis; Montero‐Odasso, Manuel; Marín‐Epelde, Itxaso; Ramón‐Espinoza, Fernanda; Zambom‐Ferraresi, Fabricio; Petidier‐Torregrosa, Roberto; Elexpuru‐Estomba, Jaione; Álvarez‐Bustos, Alejandro; Galbete, Arkaitz; et al.
Abstract: Background: Physical exercise is an effective strategy for preserving functional capacity and improving the symptoms of frailty in older adults. In addition to functional gains, exercise is considered to be a cornerstone for enhancing cognitive function in frail older adults with cognitive impairment and dementia. We assessed the effects of the Vivifrail exercise intervention for functional capacity, cognition, and well‐being status in community‐dwelling older adults. Methods: In a multicentre randomized controlled trial conducted in three tertiary hospitals in Spain, a total of 188 older patients with mild cognitive impairment or mild dementia (aged >75 years) were randomly assigned to an exercise intervention ( n = 88) or a usual‐care, control ( n = 100) group. The intervention was based on the Vivifrail tailored multicomponent exercise programme, which included resistance, balance, flexibility (3 days/week), and gait‐retraining exercises (5 days/week) and was performed for three consecutive months (http://vivifrail.com ). The usual‐care group received habitual outpatient care. The main endpoint was change in functional capacity from baseline to 1 and 3 months, assessed with the Short Physical Performance Battery (SPPB). Secondary endpoints were changes in cognitive function and handgrip strength after 1 and 3 months, and well‐being status, falls, hospital admission rate, visits to the emergency department, and mortality after 3 months. Results: The Vivifrail exercise programme provided significant benefits in functional capacity over usual‐care. The mean adherence to the exercise sessions was 79% in the first month and 68% in the following 2 months. The intervention group showed a mean increase (over the control group) of 0.86 points on the SPPB scale (95% confidence interval [CI] 0.32, 1.41 points; P < 0.01) after 1 month of intervention and 1.40 points (95% CI 0.82, 1.98 points; P < 0.001) after 3 months. Participants in the usual‐care group showed no significant benefit in functional capacity (mean change of −0.17 points [95% CI −0.54, 0.19 points] after 1 month and −0.33 points [95% CI −0.70, 0.04 points] after 3 months), whereas the exercise intervention reversed this trend (0.69 points [95% CI 0.29, 1.09 points] after 1 month and 1.07 points [95% CI 0.63, 1.51 points] after 3 months). Exercise group also obtained significant benefits in cognitive function, muscle function, and depression after 3 months over control group ( P < 0.05). No between‐group differences were obtained in other secondary endpoints ( P > 0.05). Conclusions: The Vivifrail exercise training programme is an effective and safe therapy for improving functional capacity in community‐dwelling frail/prefrail older patients with mild cognitive impairment or mild dementia and also seems to have beneficial effect on cognition, muscle function, and mood status.